2021
DOI: 10.1186/s13071-021-04710-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A levels and alpha 2 and gamma globulins on serum protein electrophoresis in cats exposed to and infected with Leishmania infantum

Abstract: Background Dogs are the main reservoir hosts of Leishmania infantum; nevertheless, recent investigations indicate a likely role for cats in the epidemiology of Leishmania infection. Feline leishmaniosis (FeL) remains poorly characterised, partly due to the lack of suitable diagnostic tools. This study aimed to compare serum amyloid A (SAA) levels and serum protein electrophoresis (SPE) profiles (specifically, alpha 2 and gamma globulins) in cats naturally exposed to or infected by L. infantum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In comparison to CanL, there is limited information about clinicopathological abnormalities associated with L. infantum infection in cats [ 41 , 57 , 97 ]. Of the cases analyzed here, hyperproteinemia (46.3%) was the most frequent laboratory abnormality, and hypergammaglobulinemia (71.0%) followed by hypoalbuminemia (19.1%) were the most frequent alterations seen on serum protein electrophoresis, in agreement with the results of two studies [ 41 , 57 ], but in contrast with those of another study [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to CanL, there is limited information about clinicopathological abnormalities associated with L. infantum infection in cats [ 41 , 57 , 97 ]. Of the cases analyzed here, hyperproteinemia (46.3%) was the most frequent laboratory abnormality, and hypergammaglobulinemia (71.0%) followed by hypoalbuminemia (19.1%) were the most frequent alterations seen on serum protein electrophoresis, in agreement with the results of two studies [ 41 , 57 ], but in contrast with those of another study [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of cats presenting with neutrophilia, thrombocytopenia, proteinuria, and azotemia (18%, 16.6%, 15.2% and 14.9%, respectively) reported in the present study suggest that leishmaniosis should be a differential diagnosis for hypergammaglobulinemic cats with any of these conditions. However, although gamma globulin levels were significantly elevated in FeL, they could not be used to differentiate FeL from other inflammatory, neoplastic or vector-borne diseases in cats [ 97 ]. Furthermore, we report here the important finding that, in FeL, unlike in CanL, azotemia and proteinuria are frequently concurrent [ 98 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for dogs, interferon gamma (IFN-γ) analysis in cat's blood could provide a better estimation of cat exposure to the disease when it is associated to serological and molecular tests [48,82]. Recently, Savioli et al (2021) and Urbani et al (2020) showed that elevated levels of amyloid A, gamma globulins, and alpha 2 globulins could be a good indicator of disease in cats [83,84], although more studies will be necessary to find definitive markers of disease.…”
Section: Diagnosis Of Flmentioning
confidence: 99%
“…However, the description of the serum protein electrophoresis and the pattern detected in cats infected with L. infantum is variable. Some authors detected monoclonal gammopathy in a cat with clinical disease (Pennisi et al, 2004), while other authors detected polyclonal gammopathy (Fernández-Gallego et al, 2020;Savioli et al, 2021).…”
mentioning
confidence: 99%